2021
DOI: 10.1088/1755-1315/682/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for addressing the impact of COVID-19 on infrastructure projects

Abstract: The COVID-19 pandemic has affected the overall economy and the construction industry badly. The Movement Control Order (MCO) caused the suspension of the construction sector, including infrastructure projects. Contractors are suffering losses and facing many problems caused by the pandemic, even with the on-going government financial aids. By identifying the right approaches to improve existing government policies and strategies, contractors could better manage the problems. Thus, this research aims to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 6 publications
2
32
1
1
Order By: Relevance
“…Meanwhile, all three CPI were not identified in the other two studies from the same locality (Zamani et al, 2021;King et al, 2021). The differences can be attributed to the nature of the different data collection approach between this study and those other works.…”
Section: Comparison With Other Studiescontrasting
confidence: 66%
“…Meanwhile, all three CPI were not identified in the other two studies from the same locality (Zamani et al, 2021;King et al, 2021). The differences can be attributed to the nature of the different data collection approach between this study and those other works.…”
Section: Comparison With Other Studiescontrasting
confidence: 66%
“…• For housing projects: While government enforcements enhanced the safety on construction projects and limited the spread of COVID-19, the order affected project progressions in terms of time delays, cost overruns, declined workforce and excessive layoffs, and limited resource availability Esa et al (2020) • For infrastructure projects: The increase in uncertainties in mega projects led to different consequences varying between financial matters such as lack of overhead costs to keep companies running due to delayed payments, and productivity matters due to lack of materials and labor shortage King et al (2021) • Other disruptions included delays in project timelines due to late authority approvals, reduced labor since foreign workers had to leave while no new workers were able to enter the country, and material delays due to crosscountry procedures and suppliers running short of supplies Zamani et al (2021) Nigeria Interviews…”
Section: Country Means Insightsmentioning
confidence: 99%
“…After receiving 127 survey responses from the architectural, engineering, and construction organizations, the authors were able to identify many effects, such as reduced foreign investment in the industry, lower demand of construction-related projects, disruption in the construction supply chain, or lower productivity. The same authors investigated the effects of the pandemic on infrastructure projects [13] using 20 phone interviews and grouping the consequences of COVID-19 in two main categories: financial and productivity. Among the main effects, the cost overrun of the projects due to the implementation of the safety operating procedures, problems and delays in the supply chain mechanism, or labor shortages may be counted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After analyzing the existing literature, a multitude of studies were found relevant as a baseline of knowledge in terms of COVID-19 main effects on the construction sector, countermeasures applied in the industry and their implementation, usage of the information technologies in the pandemic context, and digitalization. The delays that occur inside the building industry due to the anti-COVID-19 spreading regulations and to the lockdown measures have been reported by many researchers [7,11,13] as having a high impact on the sector. Their effects are propagated in many directions, such as material supply, planning, or labor shortages.…”
Section: Literature Reviewmentioning
confidence: 99%